Dél-Dunántúl agrárgazdaságának helyzetképe, lehetőségei - Weber, Erika (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
Basis of my research is the Southern Transdanubian Region. The statistical analysis showed that output, commensurable to the region's territory, can be performed only by the agricultural production. The Southern Transdanubia is the most important producer of corn and cereals, as well as in growth of sugar beet and soya in the country, and it has prominent role in growth of sunflower and rape, as well as in producing qualitative red wine. The significance of the agricultural sector is shown by the fact that despite the decrease of the food sector's importance, the food industry is the largest sector beside the energetics industry in the region. However, the competitiveness of the sector is not adequate, increase of which is essential from the aspect of the industry. One of the instruments is integration of the small growers.